PENGGUNAAN MEDIA PEMBELAJARAN SASTRA BAGI GURU BAHASA INDONESIA - Asih Riyanti; Inung Setyami (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
The Use of Media for Literature Learning for Indonesian Language Teachers. This study aims to describe the use of literary learning media for Indonesian language teachers in Tarakan Junior High School. This research uses qualitative approach. Data obtained through questionnaires, observations, and interviews. Data analysis is done through data reduction, presentation, and inference (conclusions). From the results of research it is found that most of the Indonesian language teachers who teach literature in Junior High School using media audio, visual and audiovisual are limited.